SO2 Mitigation via Catalytic Oxidation using Carbonaceous Materials and Metal Oxides for Environmental Sustainability - Edward, Tanoko Matthew; Weng, Ying; Lai, Sin Yuan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
The high concentration of sulfur dioxide (SO2) in the air that contributes to increasing health and environmental issues has caught the attention of all countries. Numerous tactics to regulate and lower the SO2 levels in the environment that have been applied through regulations and promising technology, progress has been obtained to decrease the SO2 concentration. Among methods for SO2 removal, one of the promising techniques used is the catalytic oxidation of SO2 to SO3, which not only reduces the SO2 concentration in the environment but also produces sulfuric acid (H2SO4). Thus, the performance of the catalysts that can promote the catalytic oxidation of SO2 to SO3 for environmental sustainability is reviewed in this study. The types of catalysts evaluated in this study are carbon-based materials and metal oxides. Worth noting that these catalysts are feasible to catalytically converting SO2 hazardous material to resources, viz. SO3 and H2SO4 for industrial use. The findings of this study can serve as a foundation for devising an innovative method for SO2 mitigation through catalytic oxidation. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).